Assessment and Documentation of Indigenous and Introduced Soil and Water Conservation Practices in the Case of Silte and Gurage zone, SNNPR, Ethiopia (Global Journal of Science Frontier Research, 2020)
Soil erosion is the most limiting environmental factor for crop production in Ethiopia, particularly Southern Regional State. To reverse the land degradation problem, many indigenous and introduced soil and water conservation interventions were implemented in different parts of Ethiopia. However, this practice is not well documented and known in South-central zones. The current study has been initiated to assess the indigenous and introduced soil and water conservation practices in the Gurage and Silte zone. As a method; Key informant interview, Focused group discussion, observation through transect walk was used as a source of data. Key informant interviews has been conducted at zonal and woreda level to group two representative woredas per zone and three representative kebeles per woreda. Based on the key informant interviews, Sankura and Alicho-wuriro woreda from the Silte zone, whereas Meskan and Gummer woreda from the Gurage zone was selected based on their adoption potential of both indigenous and introduced soil and water conservation practices.
Keywords: FGD; indigenous SWC; introduced SWC; soil and water conservation; soil erosion